Differential expression of glutamate transporters EAAT1 and EAAT2 in mice deficient for PACAP-type I receptor - Zink, Mathias; Schmitt, Andrea; Henn, Fritz A.; Gass, Peter (Journal of neural transmission, 2004)
Pituitary adenylate cyclase-activating polypeptide (PACAP) modulates glutamatergic neurotransmission and induces the expression of glutamate transporters EAAT1 and EAAT2 in newborn mouse astroglial cell cultures. Since nanomolar concentrations of PACAP exert this effect, signal transduction via the high affinity PACAP-type I-receptor PAC1 was assumed. To test this hypothesis and to assess the importance of PAC1-signalling in vivo, we analyzed glutamate transporter expression in mice with a PAC1 knockout.
Gesehen am 12.11.2020